2018
DOI: 10.1093/cid/ciy183
|View full text |Cite
|
Sign up to set email alerts
|

Sex Difference in Meningococcal Disease Mortality, New York City, 2008–2016

Abstract: Female mortality from IMD was significantly increased compared with males, controlling for other predictors of mortality. Sex-based differences in recognition and treatment need to be evaluated in cases of meningococcal disease. Our study highlights the importance of analyzing routine surveillance data to identify and address disparities in disease incidence and outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 35 publications
0
7
1
Order By: Relevance
“…There is evidence that the IR for meningococcal disease differ between the sexes, based on population-based studies, case series and case−control studies [11][12][13][14][15]. In addition, in several studies case-fatality rates were higher among females [16][17][18]. On the other hand, female infants appear to develop a stronger immune response to group C meningococcal vaccine [19].…”
Section: Introductionmentioning
confidence: 99%
“…There is evidence that the IR for meningococcal disease differ between the sexes, based on population-based studies, case series and case−control studies [11][12][13][14][15]. In addition, in several studies case-fatality rates were higher among females [16][17][18]. On the other hand, female infants appear to develop a stronger immune response to group C meningococcal vaccine [19].…”
Section: Introductionmentioning
confidence: 99%
“…But another study regarding invasive meningococcal disease in New York City found that the mortality rate of female patients with hydrocephalus was 13 times that of male, which the author speculated that it may be related to differences in immune response due to sex hormone level. 21 Our study showed that female sex was a predictor for hydrocephalus, but female patients did not exhibit a worse outcome than male patients at discharge. Therefore, our results only suggest that female newborns are more likely to develop hydrocephalus in meningitis, as to whether there is a poor prognosis may require further analysis.…”
Section: Discussionmentioning
confidence: 48%
“…Another notable feature is that the CFR among females (39.5%) was much higher than for males (19.0%) in those 2 years, but the contributing risk factor was unclear. The finding of females with a higher CFR than males has been observed in New York City, NY, USA ( 38 ), but the effect of sex on mortality in IMD was not supported by the results from the surveillance data from 21 European countries ( 39 ).…”
Section: Discussionmentioning
confidence: 89%